EXAMINING THE HADITH WHICH STATES THAT SILATURAHMI CAN EXPAND SUSTENANCE AND EXTEND LIFE - Siti Jubaedah; Mus'idul Millah (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2021)
This article will study and examine the hadith of the Prophet Muhammad pbuh which states that relationship can expand sustenance and extend life. This study is very important to investigate the meaning of the hadith proportionally. The object of this research is the hadith narrated by al-Bukhari in his work al-Jami? al-?a??? in Kit?b Al-Buy??, B?b Man A?abba al-Bas? f? al-Rizq no. 2067. The literal meaning of this hadith potentially has to cause problems, because it can conflict with the concept of destiny (taqd?r). Therefore, it is important to examine the significance of the recommendation to connect the ties of relationship and the benefits that can be obtained. In this study, the hadith is no longer examined for the validity of the sanad, the study is focused on examining matan by applying the four parameters that have been compiled by al-Idlibi; 1) does not contradict the Qur'an, 2) does not contradict the stronger hadith, 3) does not conflict with common sense, senses and historical facts, 4) the composition of the statement shows the characteristics of the prophetic word. Through this research, it can be understood that the meaning of